Kontekstualisasi Nilai-Nilai Adat "Sianauang paqmai" dan "Sibaliparriq" dalam Perkawinan Masyarakat Mandar Perspektif Hukum Keluarga Islam: Contextualization of the Traditional Values of “Sianauang paqmai” and “Sibaliparriq” in Marriage Among the Mandar People: A Perspective from Islamic Family Law - Kuddus; Rusdaya Basri; Fikri (QISTHOSIA : Jurnal Syariah dan Hukum, 2026)
This study examines the contextualization of the traditional values of Sianauang paqmai and Sibaliparriq in Mandar marriage customs from the perspective of Islamic family law. It addresses three questions: the meaning and role of these values, their implementation in contemporary Mandar marriages, and their compatibility with Islamic family law. This qualitative field research employed a juridical-empirical approach, drawing on primary and secondary data. Data were collected through interviews, observations, and documentation, then analyzed descriptively through data reduction, data presentation, and conclusion drawing. The study applied the theories of urf, living law, implementation, and gender. The findings show that Sianauang paqmai and Sibaliparriq remain significant in Mandar family life. Sianauang paqmai emphasizes affection, mutual respect, emotional understanding, and constructive communication between spouses. Sibaliparriq stresses cooperation, shared responsibility, mutual support, and a balanced division of domestic and family roles. Together, these values strengthen household harmony, resilience, and continuity. In contemporary practice, both values continue to be reflected in mutual care, respect, cooperation, and the sharing of responsibilities between husband and wife. Their relevance remains strong today. From the perspective of Islamic family law, their implementation is consistent with Sharia principles because it promotes love, justice, cooperation, and collective responsibility within marriage. The novelty of this study lies in positioning Sianauang paqmai and Sibaliparriq as forms of living law. They are not merely preserved as Mandar cultural heritage, but are also contextualized as customary values that support and reinforce the principles of Islamic family law in contemporary marital life.